Abundancia de bacterias productoras de Polihidroxialcanoato en suelos de la región andina de Nariño, Colombia - Fernández Izquierdo, Pablo; Bravo Benavides, Daniel Augusto (Universidad y Salud, 2009)
There is a lot of information and studies about the biochemical aspects and the molecular bases of the enzymatic process involved in the synthesis of Polyhydroxyalkanoates (PHAs), as well as in the polymer degradability and methods for increasing the production at an industrial level. Nevertheless, there is little research related to the ecological factors of the PHAs producer bacteria. For this reason, the effect of the physicochemical soil variables in the PHAs producer bacteria abundance. In this research, it was established that the PHAs producer bacteria abundance in soils in the Andean region of Nariño in Colombia is connected with high concentrations of carbon, nitrogen, high capacity of cation interchange and acid pH. Among the PHAs producer bacteria abundance isolated from soils in this region, the 71, 1% syntheses Polyhydroxybutyrate and the 28,9% accumulates the copolymer Poly (3hydroxybutyrate-co-3-hydroxyvalerate).